Primary Systemic Amyloidosis - Syed, Maria; Ahmad, Afaq; Haque, Anwar Ul (International Journal of Pathology, 2018)
Primary systemic amyloidosis is a rare entity. We report a case of primary systemic amyloidosis withoutany associated hematological abnormality who presented with macroglossia and hemorrhagic lesions aroundeyes and sub mammary region. There were soft lobulated masses around perianal region, labia majora and on externalauditory meatus obstructing auditory canal. She was also operated for carpel tunnel syndrome in thepast.Urine and serum electrophoresis were negative. Diagnosis was confirmed by biopsy of submammary skin lesionusing haematoxylin and eosin and Congo red stain. Polarized microscopy was used to see birefringence of amyloid.